Peran ‘Aisyiyah Pekanbaru dalam Pengembangan Pendidikan di Kota Pekanbaru (1975-2015) - Duwi Kartika; Bunari Bunari; Ahmal Ahmal (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
This study aims to analyze the role of Aisyiyah in the development of education in Pekanbaru City in 1975-2015, so as to find out the background of the establishment of Aisyiyah Pekanbaru. Aisyiyah as a special Autonomy organization for Muhammadiyah can foster women to be educated to become leaders, and be prepared to become administrators in Muhammadiyah women's organizations. Aisyiyah's presence in developing her educational role in Riau Province, especially in Pekanbaru City has produced strong cadres in organizing. Aisyiyah's presence in Pekanbaru is inseparable from the arrival of Muhammadiyah's understanding and thoughts. Aisyiyah is engaged in social, educational, health and religious fields. This research uses historical methods consisting of heuristics, verification, interpretation, historiography. Aisyiyah has activities with several programs, one of which is in the field of education, especially in Kindergarten (TK) Bustanul Athfal Aisyiyah, a program on worship that is guided by the Central Leadership (PP) in Jakarta on Kemuhammadiyahan and Keaisyiyahan. Based on the results of the study, it can be concluded: The presence of 'Aisyiyah in Pekanbaru is inseparable from the arrival of Muhammadiyah's understanding and thoughts. The entry of the notion of renewal (Muhammadiyah) to Pekanbaru is the establishment of da'wah and trade interactions with the surrounding area. Aisyiyah in education is concerned with Islamic children's education, providing formal and non-formal education with noble character.